Exertional compartment syndrome - Wilder, R. P.; Magrum, E. (Clinics in Sports Medicine, 2010)
Chronic exertional compartment syndrome should be considered in any runner experiencing exertional leg pain. Runners typically describe a tight, cramping ache over the involved compartment that commences at a reproducible point in the run and resolves with rest. Diagnosis should include a careful history and physical examination as well as documentation with intramuscular compartment pressure monitoring. Milder cases will resolve with activity modification and conservative care. More severe cases or those failing conservative care are referred for fasciotomy.